2018
DOI: 10.2147/cwcmr.s146747
|View full text |Cite
|
Sign up to set email alerts
|

Sharp wound debridement: patient selection and perspectives

Abstract: Conservative sharp wound debridement, as part of the wound bed preparation paradigm, can be performed in a wide variety of settings including the patients' home or community clinic settings, by health care professionals who perform within their scope of practice and have been certified to be competent. This paper reviews the components that must be in place to ensure safe delivery of conservative sharp wound debridement for an increased number of clinicians, with organizational support, based on practices in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…The longest established method of biofilm eradication from chronic wounds is debridement (Yazdanpanah et al 2015), which has been found to expedite wound healing and reduce the overall size of a wound (Rhoads et al 2008). However, complete wound healing requires multiple invasive treatments, typically carried out over a period of months (Harris et al 2018;Michailidis et al 2018). Although the efficacy of debridement can be increased with the use of chemicals such as hydrogen peroxide or certain enzymes (Watters et al 2016), failure to remove biofilm persister cells from the wound bed is a common cause of recalcitrance (Percival et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The longest established method of biofilm eradication from chronic wounds is debridement (Yazdanpanah et al 2015), which has been found to expedite wound healing and reduce the overall size of a wound (Rhoads et al 2008). However, complete wound healing requires multiple invasive treatments, typically carried out over a period of months (Harris et al 2018;Michailidis et al 2018). Although the efficacy of debridement can be increased with the use of chemicals such as hydrogen peroxide or certain enzymes (Watters et al 2016), failure to remove biofilm persister cells from the wound bed is a common cause of recalcitrance (Percival et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini dianggap sebagai standar perawatan dan dilakukan berulang kali (Thomas et al, 2021). Tujuan melakukan CSWD adalah untuk menghilangkan non-viable jaringan sehingga mencapai dasar luka yang lebih bersih, dengan peningkatan dalam persentase jaringan yang layak, penurunan jumlah luka eksudat, penurunan risiko infeksi luka dan bau busuk (Harris et al, 2018).…”
Section: Pendahuluanunclassified
“…Setelah jaringan nekrotik diangkat kemudian inflamasi sudah berhenti maka luka akan masuk ke fase proliferasi dan mulai membentuk jaringan granulasi. Saat itulah proses perbaikan luka akan dimulai (Harris et al, 2018).…”
Section: Tinjauan Pustakaunclassified
“…We should assess the wound using a validated wound assessment tool such as the Bates-Jensen Wound Assessment tool [2]. Skin grafting can be done in the presence of well-vascularized peritendon and periosteum.…”
Section: Recipient Site Considerations 21 Wound Bed Preparationmentioning
confidence: 99%
“…Conservative Sharp Wound Debridement (CSWD) is a suitable method of debridement when there is dead necrotic tissue such as slough or eschar, callustissue around the wound, or hyperkeratosis (which is clearly demarcated from the healthy tissue, where other types of debridement may not give optimum result and/or where speed is essential) [2].…”
Section: Recipient Site Considerations 21 Wound Bed Preparationmentioning
confidence: 99%